Fostering humanism: a mixed methods evaluation of the Footprints Project in critical care. Issue 11 (2nd November 2019) - Hoad, Neala; Swinton, Marilyn; Takaoka, Alyson; Tam, Benjamin; Shears, Melissa; Waugh, Lily; Toledo, Feli; Clarke, France J; Duan, Erick Huaileigh; Soth, Mark; Cook, Deborah J
Abstract : Objectives: The objectives of this mixed-methods study were to assess the uptake, sustainability and influence of the Footprints Project. Setting: Twenty-two-bed university-affiliated ICU in Hamilton, Canada. Participants: ICU patients admitted and their families, as well as clinicians. Interventions: We developed a personalised patient Footprints Form and Whiteboard to facilitate holistic, patient-centred care, to inform clinical encounters, and to create deeper connections among patients, families and clinicians. Outcome measures: We conducted 3 audits to examine uptake and sustainability. We conducted semi-structured interviews with 10 clinicians, and held 5 focus groups with 25 clinicians; and we interviewed 5 patients and 13 family representatives of 5 patients who survived and 5 who died in the ICU. Transcripts were analysed using qualitative content analysis. Results: The Footprints Project facilitated holistic, patient-centred care by setting the stage for patient and family experience, motivating the patient and humanising the patient for clinicians. Through informing clinical encounters, Footprints helped clinicians initiate more personal conversations, foster deeper connections and guide treatment. Professional practice influences included more focused attention on the patient, enhanced interdisciplinary communication and changes in community culture. Initially used in 15.8% of patients (audit A), uptake increased to 51.4% in audit B, and was sustained at 57.8% in audit C. Conclusions: By sharing valuable personal information about patients before and beyond their illness on individualised whiteboards at each bedside, the Footprints Project fosters humanism in critical care practice.